Direct speech in Nonnus' Dionysiaca : narrative and rhetorical functions of the characters' "varied" and "many-faceted" words - Verhelst, Berenice, 1987- (Mnemosyne, Supplements, 2016)
Direct Speech in Nonnus' Dionysiaca is the first more extensive study of the use and functions of direct speech in Nonnus' Dionysiaca (5th century AD). Its long soliloquies and scarcity of dialogues have often been pointed out as striking characteristics of Nonnus' epic style, but nonetheless this fascinating subject received relatively little attention. Berenice Verhelst aims to reveal the poem's constant interplay between the epic tradition and the late antique literary context with its clear rhetorical stamp. She focusses on the changed functions of direct speech and their implications for the presentation of the mythological story. Organized around six case studies, this book presents an in-depth analysis of a representative part of the vast corpus of the Dionysiaca's 305 speeches. The digital appendix to this book ( Database of Direct Speech in Greek Epic Poetry ) can be consulted online at www.dsgep.ugent.be .